Continuous Fields with Fibres $\mathscr{O}_{∞}$ - Blanchard, Etienne (MATHEMATICA SCANDINAVICA, 2014)
We study in this article a class of unital continuous $C^*$-bundles the fibres of which are all isomorphic to the Cuntz $C^*$-algebra $\mathscr{O}_{∞}$. This enables us to give several equivalent reformulations for the triviality of all these $C^*$-bundles.